One-fourth of the prisoners are underweight in Northern Ethiopia: a cross-sectional study - Semaw Ferede Abera; Kelemework Adane (BMC, 2017)
Abstract Background Despite the fact that prisoners are exposed to different health problems, prison health problems are often overlooked by researchers and no previous study has investigated nutritional problems of prisoners in Ethiopia. Methods Cross-sectional data were collected from 809 prisoners from nine major prison setups in the Tigray region of Ethiopia. A proportional stratified sampling technique was used to select the total number of participants needed from each prison site. The outcome of this study was underweight defined as body mass index (BMI) of less than 18.5 kg/m2. Multivariable binary logistic regression was performed to identify determinants of underweight at a p-value of less than 0.05. Results The prevalence of underweight was 25.2% (95% CI; 22.3%- 28.3%). Khat Chewing (OR = 2.08; 95% CI = 1.17, 3.70) and longer duration of incarceration (OR = 1.07; 95% CI = 1.01, 1.14) were associated with a significantly increased risk of underweight. Additionally, previous incarceration (OR = 1.54; 95% CI = 0.99, 2.42) was a relevant determinant of underweight with a borderline significance. In contrast, family support (OR = 0.61; 95% CI = 0.43, 0.85) and farmer occupation (OR = 0.59; 95% CI = 0.36, 0.98) compared to those who were unemployed were important protective determinants significantly associated with lower risk of underweight. Conclusion In summary, the burden of underweight was higher among prisoners in Tigray region who had respiratory tract infections. The study has enhanced our understanding of the determinants of underweight in the prison population. We strongly recommend that nutritional ﻿support﻿, such as therapeutic feeding programs for severely or moderately underweight prisoners, and environmental health interventions of the prison setups should be urgently implemented to correct the uncovered nutritional problem and its associated factors for improving the health status of prisoners.